Úvahy o právech přirozených a lidských - Pinz, Jan (Univerzita Pardubice, 2000)
The focus is on a brief historical survey of the evolution, including recent analysis, of natural rights and human rights. In conclusion, a comparison between ius positivum and ius humanum is provided.
Keywords: Lidská práva; přirozené právo; filosofické hledisko